Adolescents' reactions to participating in ethically sensitive research: a prospective self-report study. Issue 1 (December 2015) - Hasking, Penelope; Tatnell, Ruth; Martin, Graham
Abstract Background Conducting psychological research with adolescents is imperative for better understanding, prevention and treatment of mental illness. However there is concern that research addressing topics such as mental illness, substance use and suicidality has potential to distress participants, particularly youth. Method We administered a questionnaire to 1973 adolescents (13–18 years) at two time points, one year apart. Participants responded to items regarding nonsuicidal self-injury, psychological distress, history of physical and/or sexual abuse, adverse life events, alcohol use, suicidal behaviour, self-efficacy, and coping skills as well as two open-ended questions regarding whether they enjoyed participating in the research and whether participation worried or upset them. Results Most youth (74 %) enjoyed participation and cited altruistic reasons and a greater self-awareness as reasons. Those reporting being upset by the questionnaire (15 %) reported poorer psychological functioning than their peers. Youth who were upset by their participation at baseline, but who reported enjoying the questionnaire at follow-up reported improved psychosocial functioning over time, while the reverse was true for those who initially enjoyed participation but later reported the questionnaire upset them. Conclusions Results suggest researchers acknowledge benefits for young people who participate in research, but also be mindful of the potential for distress among the most at risk youth.